Analysis of Annual SPT Reporting on Final Income From Construction Services at PT Parama Murti - KASIAHENG, Wisnur Rianti; SONDAKH, Jullie Jeanette; AFANDI, Dhullo (PT Keberlanjutan Strategis Indonesia, 2024)
Tax Return (SPT) is a letter used by taxpayers to report tax calculations and payments, taxable and non-taxable objects, and assets and liabilities according to the provisions of tax laws and regulations. This study aims to analyze the reporting of the Annual Tax Return (SPT) carried out by PT Parama Murti whether it is in accordance with Law No. 7 of 2021 concerning Harmonization of Tax Regulations. The type of research used is qualitative research with the research method used is a descriptive method whose data is obtained from interviews and documentation. The results of this study indicate that the reporting of the Annual SPT carried out is not fully in accordance with the applicable laws and regulations, where in the reporting of the Annual SPT there are attachments that are not made by the company and errors in the preparation of the SPT cause the submission of the SPT to be considered incomplete.